Colorectal cancer-derived exosomal miR-106b-3p promotes metastasis by down-regulating DLC-1 expression. (27th February 2020) - Liu, He; Liu, Yanlong; Sun, Ping; Leng, Kaiming; Xu, Yi; Mei, Liqi; Han, Peng; Zhang, Bomiao; Yao, Kefei; Li, Chunbo; Bai, Junge; Cui, Binbin
Abstract: Cancer-derived exosomal miRNAs play an important role in the development of metastasis, but the effects and underlying mechanisms remain unclear. In the present study, we investigated the miRNA expression profiles of 5 paired serum exosomal samples from metastatic colorectal cancer (mCRC) and non-mCRC patients via RNA sequencing. After we evaluated the differentially expressed miRNAs in 80 CRC patients, miR-106b-3p was selected as a metastasis-associated miRNA of CRC. We showed that the expression level of serum exosomal miR-106b-3p was significantly higher in CRC patients with metastasis than those without metastasis. Additionally, high serum exosomal miR-106b-3p expression in patients was correlated with a poor prognosis. Coculture of low-metastatic CRC cells with high-metastatic CRC cell-derived exosomes promoted cell migration, invasion, and epithelial-to-mesenchymal transition (EMT), which was caused by the transport and transduction of miR-106b-3p in vitro . Moreover, exosomal miR-106b-3p promoted lung metastasis of CRC cells in vivo . In addition, we demonstrated that miR-106b-3p regulated metastasis by targeting deleted in liver cancer-1 (DLC-1). A negative correlation was also identified between miR-106b-3p and DLC-1 expression in human CRC tumour tissues and in mouse lung metastatic lesions. Collectively, our study indicated that metastasis-associated miR-106b-3p from serum exosomes could be used as a potential prognostic biomarker and therapeutic target for CRC patients.